Dynamics of Torsional Vibration Damper (TVD) pulley, implementation of a rubber elastomeric behavior, simulations and experiments. (December 2019) - Silva, C.A.F.; Manin, L.; Rinaldi, R.G.; Besnier, E.; Remond, D.
Highlights: Implementation of a viscoelastic behavior for the Torsional Vibration Damper model. Dynamic Mechanical Analysis and thermo-simplicity principle were applied. Temperature and frequency dependencies of the rubber-ring viscoelastic properties. Experimental/simulation comparisons of FRFs under several operating conditions. Abstract: In this work, the Torsional Vibration Damper (TVD) rubber ring viscoelastic-material properties are determined based on Dynamical Mechanical Analysis (DMA) measurements and master curves reconstructions using thermo-simplicity principle. The elastomeric constitutive behavior is then implemented in the torsional vibration damper's equation of motion and the frequency response is simulated so that enhanced physical representation of the TVD dynamics can be achieved. Major differences in the TVD frequency response are highlighted and analyzed whether or not the viscoelastic material properties (elasticity modulus and damping) are considered constant or frequency and temperature dependent.